PENGELOLAAN PAJAK TAMBANG GALIAN GOLONGAN C DAN IMPLIKASINYA TERHADAP PENINGKATAAN PENDAPATAN ASLI DAERAH DI KABUPATEN SIDENRENG RAPPANG - Darmawan, Darmawan; Sampara, Nirwana; Hatta, Muh (Cateris Paribus Journal, 2021)
Regional Income is one indicator that determines the degree of independence of a region. This study aims to determine the Management of Mining Tax Group C and its implications for increasing local revenue in Sidenreng Rappang Regency and to determine the factors that influence the management of Mining Tax Group C on increasing local revenue in Sidenreng Rappang Regency. The data collection techniques used in this research are library research methods and field research consisting of observations, interviews, and questionnaires (questionnaires). The sample in this study amounted to 37 people using the purposive sampling technique. This study uses technical data analysis in the form of a frequency table, using a Likert scale as a measuring tool. Mining Tax Management Group C as a whole belongs to the good category but from 4 (four) indicators consisting of planning (72.25%), organizing (70.25%), implementation (70.25%), which has a low category there are on the monitoring indicator (54.5%) so it still needs to be improved. The factors that influence the Group C Mining Tax on Increasing Regional Original Income in Sidenreng Rappang Regency are Apparatus Knowledge About Organizational Principles (81.75%), High Work Discipline (58.75%), Facilities and Infrastructure (50%) Taxpayer Community Participation (58%), Law (72.25%) and Economics (66%).